2019
DOI: 10.17851/1983-3652.12.3.16-36
|View full text |Cite
|
Sign up to set email alerts
|

Evolución científica de la enseñanza de lenguas en el contexto universitario (1900-2019)

Abstract: RESUMEN: Este artículo tiene por objetivo analizar la evolución de la investigación sobre enseñanza de lenguas en el ámbito universitario dentro de la colección principal de la Web of Science (1900-2019). Para ello, se ha desarrollado un estudio bibliométrico por revisión sistemática, tomando en consideración los siguientes indicadores: producción diacrónica, geográfica, autores y de fuente. A su vez, se ha realizado un análisis del desarrollo estructural de los temas sobre una muestra de 2978 referencias proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…The novelty presented by this study, with respect to other works with the same intention [36], comes from the bibliometric analysis technique used. This technique not only focuses on the quantification of bibliometric indicators, but also on the dynamic and structural development of the delimited constructs, as reflected in other works [37,38]. Therefore, this research helps to reduce the gap found in the impact literature of this field of knowledge, by not finding any study of the same characteristics as the one presented in this manuscript.…”
Section: Justification and Objectivesmentioning
confidence: 87%
“…The novelty presented by this study, with respect to other works with the same intention [36], comes from the bibliometric analysis technique used. This technique not only focuses on the quantification of bibliometric indicators, but also on the dynamic and structural development of the delimited constructs, as reflected in other works [37,38]. Therefore, this research helps to reduce the gap found in the impact literature of this field of knowledge, by not finding any study of the same characteristics as the one presented in this manuscript.…”
Section: Justification and Objectivesmentioning
confidence: 87%
“…To this end, firstly, analytical tracking and documentary quantification techniques have been used to evaluate research performance in the field of study [65] specified in the section on Procedure and Data Analysis. Secondly, scientific mapping has been carried out [66] to find out the particular and general themes of the research, as well as their thematic evolution [67]. This scientific mapping takes as main references, the h index and the number of citations [68], and as secondary indicators, the g, hg and q2 indexes [69], trying to offer as much information as possible about the metrics of the field of study [70].…”
Section: Methodsmentioning
confidence: 99%
“…The author relates this to a researcher [2] who argued that writing enables learners to analyze and consolidate second language (hereinafter, L2) knowledge. Students focus on the relationship between form and meaning, and, consequently, work in order to express their ideas by using language in the most accurate way possible [3]. This author found that in writing tasks, a "type of linguistic processing" takes place, which is an important source for second language learning (hereinafter, SLL).…”
Section: Introductionmentioning
confidence: 99%